Development of methodological and organizational approach to determine the cost of construction through the use of variant design - Purs, G. A.; Mikhalkevich, N. M. (Ways to Improve Construction Efficiency, 2019)
The most important step in the implementation of the multi-stage modernization of the pricing system in the construction complex was the development of methodological and organizational approaches to determining the cost of construction through the use of variant design, which allows the customer to see all possible ways of building a building or structure, to determine the most cost-effective options and ways to reduce labor. The article is devoted to the study of the reasons for the need to improve the pricing system of the construction industry and the introduction of an analogous method of determining the cost of construction at the stage of investment substantiation and development of an architectural project, to study the base of regulatory documents aimed at the implementation of the analogous method of forming the estimated cost of construction. The article also discusses perspective directions for the use of analog objects and directions for the further development of analog objects as a tool for calculating the cost of construction based on information modeling of buildings. The economic effect of the use of analogues to determine the cost of construction at the pre-investment stage is achieved by reducing the duration of the formation of estimated documentation, increasing the reliability of calculations of estimated value at current prices when substantiating investments and developing an architectural project, as well as by creating an information basis for the implementation of variant design . The Data Bank of Analog Objects provides an opportunity to quickly and adequately evaluate the required volume of investments with the development of several alternative design and volume planning solutions. The automated information-analytical system proposed for development will allow to calculate the cost of construction on the basis of the information base of the republican bank of data of objects of analogues. This calculation covers all costs that the customer must incur in order to get the facility ready for operation. In addition, the level of accuracy of the obtained data will allow you to orient the customer with regard to the volume of investments expected to be used in the planning of their business activities for the long term.